The use of Memrise Application in Improving Students' Vocabulary Mastery at the 8th grade of Junior High School - Ramadhanti Dian Zuniati; Tarcisia Sri Suwarti; Ajeng Setyorini (Lembaga Pengembangan Kinerja Dosen, 2023)
The ability to master English is one of the most important things for students in junior high school. Vocabulary mastery is important for students to succeed in learning and mastering English. The main purpose of this research was to find out whether there was any significant difference between students' vocabulary mastery before and after taught using Memrise application. The researcher used quantitative research and applied a pre-experimental design with a one-group pre-test and post-test. The sample consisted of 30 students. The researcher used SPSS to analyze the t-test. From the analysis, it showed that the value of Sig. (2-tailed) is 0.000 < 0.05. Based on the analysis of the t-test and t-table value, it shows that the t-test score is 11,128, and the t-table value is 1.699. It means that the t-test value is higher than the t-table. It means that there is a significant difference between pre-test and post-test scores. Thus, it can be interpreted that the alternative hypothesis (Ha) was accepted the null hypothesis (Ho) was rejected.Thus, Teaching vocabulary using the Memrise application can improve students' vocabulary mastery. Therefore, the Memrise application is suitable to use as a media for learning and teaching English vocabulary.